Burnt forest clear-cuts, a breeding habitat for ortolan bunting Emberiza hortulana in northern Sweden? - Lucas, Cloé (2014)
The Ortolan Bunting population has decreased in Sweden by about 80 % since 1975. Nowadays, the largest part of the Ortolan Bunting population occurs on the northern coast where the majority breeds on clear-cuts. The aim of the study was to describe the Ortolan Bunting breeding habitat characteristics in northern Sweden to provide a basis for management plan. In Phase 1, I investigated if Ortolan Buntings were more present on prescribed burnt clear-cuts than on non-burnt clear-cuts with a presence/absence survey. Unfortunately the occupancy rate in the study area appeared to be very low. As a second step, I extended the study on habitat characteristics within a study area closer to the coast (Phase 2). There was a positive relationship between clear-cut size and Ortolan Bunting presence, but when accounting for random spatial distribution, presences on small clearcuts were as common or even higher as on large ones. Proximity to farmland had no significant effect on presence of Ortolan Bunting. These two conclusions may be explained by the fact that Ortolan Buntings had the possibility to use multiple clear-cuts and thus find additional resources on a nearby clear-cut, relaxing resource shortage on the clear-cut of the nesting territory. Within 70 km from the coast, there was no coast-inland gradient in Ortolan Bunting presence. The studied parameters could not explain the low Ortolan Bunting presence in the studied area used in Phase 1 but they supplied management plan of the species by pointing out that prescribed burning did not seem to have to take into account neither clear-cut size, distance to farmland nor distance to the coast (< 70 km). This study also provided some information for future researches about the distribution of the Ortolan Bunting in the region and pointed out further questions to be considered to get a global vision of Ortolan Bunting breeding habitat in the region.